The Turning of the Tide: Theology, Religion, and Economics1. (1st March 2013) - Rieger, Joerg
<x xml:space="preserve">Abstract</x> Abstract: Although capitalist free market economics is in crisis, its assumptions continue to shape not only how we do business or politics but also how we think and feel, and even what we believe. For theologians and scholars of religion this means that we can no longer do our work without taking into consideration what is happening in the economy and how it affects us; before religion can become part of the solution we need to understand how it has become part of the problem. This article investigates how economics has shaped religion and theology and develops alternative perspectives.